Effectiveness of an Educational Program Regarding Vasoactive Drugs at the Level of Knowledge and Practices among Nurses Working in Critical Care Units - Ibtisam Al-Zaru; Anas Mohammad (Jordan University of Science and Technology, 2022)
Background: Critical care unit nurses have the responsibility of medication preparation and administration. Vasoactive drugs are lifesaving that commonly used in critical care units. However, the inappropriate administration of vasoactive drugs may lead to poor patient outcomes and complications. Purpose: The present study aimed to evaluate the effectiveness of educational program of vasoactive drugs administration on critical care unit nurses' knowledge and practice Methods: A one-group pretest-posttest design was used for this study. A convenience sample of 102 registered nurses working at different critical care units at a University Affiliated Hospital was recruited. The researcher provided the study participants with a valid educational program on knowledge and practices related to the administration of vasoactive drugs. Three tools were used to collect data, a demographics form, a vasoactive drugs knowledge questionnaire, and a vasoactive drugs observational checklist. Results: There was a significant difference in the nurses’ vasoactive drugs knowledge scores before (M=9.28, SD=2.31) and after the educational program (M=12.30, SD=1.43) with p < 0.001. Furthermore, there was a significant difference in the nurses’ total vasoactive drugs observational checklist scores before (M=18.62, SD=2.27) and after the educational program (M=23.04, SD=1.76) with P < 0.001. Experience in the current critical care unit and course-related vasoactive drugs were significant predictors of the pre-knowledge test scores. Experience in the current critical care unit was a significant predictor of the pre-practices test scores. Conclusion. The implemented educational program significantly improved critical care unit nurses’ knowledge and practices related to the administration of vasoactive drugs. Implications to Nursing: Educational program increase nurses’ knowledge, competence and confidence regarding Vasoactive drugs administration.